2022
DOI: 10.3934/krm.2021040
|View full text |Cite
|
Sign up to set email alerts
|

The Einstein-Vlasov system in maximal areal coordinates---Local existence and continuation

Abstract: <p style='text-indent:20px;'>We consider the spherically symmetric, asymptotically flat Einstein-Vlasov system in maximal areal coordinates. The latter coordinates have been used both in analytical and numerical investigations of the Einstein-Vlasov system [<xref ref-type="bibr" rid="b3">3</xref>,<xref ref-type="bibr" rid="b8">8</xref>,<xref ref-type="bibr" rid="b18">18</xref>,<xref ref-type="bibr" rid="b19">19</xref>], but neither a local existence theorem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In the singularity-free setting there exist unique, local in-time solutions for smooth, compactly supported initial data together with a continuation criterion [45,46]. Similar results are known in other coordinates, e.g., in maximal-areal coordinates [19] or maximal isotropic coordinates [50]. In the case of a Schwarzschild singularity at the center, it can be shown that the methods from [48] yield a global existence result in Schwarzschild time.…”
Section: The Einstein-vlasov System In Schwarzschild Coordinatesmentioning
confidence: 76%
“…In the singularity-free setting there exist unique, local in-time solutions for smooth, compactly supported initial data together with a continuation criterion [45,46]. Similar results are known in other coordinates, e.g., in maximal-areal coordinates [19] or maximal isotropic coordinates [50]. In the case of a Schwarzschild singularity at the center, it can be shown that the methods from [48] yield a global existence result in Schwarzschild time.…”
Section: The Einstein-vlasov System In Schwarzschild Coordinatesmentioning
confidence: 76%
“…An analogous result holds in maximal areal coordinates, cf. [8], but probably not in Eddington-Finkelstein coordinates, at least not for general smooth data whose support contains the origin. In general, Schwarzschild or maximal areal coordinates are more useful when proving that certain data launch global, geodesically complete solutions, cf.…”
Section: Properties and Comparison Of The Coordinate Systemsmentioning
confidence: 94%
“…It is also possible that other coordinates adapted to spherical symmetry are more suitable for the stability analysis. We will not pursue this issue but mention maximal areal coordinates as one alternative [35].…”
Section: The Ev Systemmentioning
confidence: 99%